Agriculture and Rural economy - Sahoo, Rajan Kumar; Sahoo, Rajan Kumar 1961-; Dash, Gyanindra, 1965- (New Delhi : Regal Publications, 2009)
Proceedings of a national seminar held at Kendrapara on 17th February 2008.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- India -- Congresses; Rural development -- India -- Congresses; Agriculture and state -- India -- Congresses